Workplace Positive Actions, Trans People's Self-Esteem and Human Resources' Evaluations - Vasiliki Bozani; Nick Drydakis; Katerina Sidiropoulou; Benjamin Harvey; Anna Paraskevopoulou (Institute of Labor Economics (IZA), 2019)
This study provides empirical patterns regarding trans people's self-esteem-oriented reflections during observations of positive workplace actions. The case of a 2015 UK workplace guide is utilized to fulfil our aims. We adopt Rawls' political philosophy framework in order to evaluate whether trans people's self-esteem-oriented concepts might be enhanced by policy makers' positive actions. The study does find that trans people's self-esteem and self-respect are enhanced by policy makers' positive actions to promote inclusivity in the workplace. Due to these actions trans people feel more accepted, valued and trusted by the government. We suggest that if a workplace policy is perceived to be recognizing trans people's worth this may be internalized, resulting in positive self-evaluations by trans people. In addition, we present empirical patterns from HR departments which have been aware of the workplace guide. HR officers suggest that the workplace guide informs their strategies, and positively affects the creation of a more inclusive workplace culture, the corporate profiles of their firms and staff organizational behaviours (such as, achieving results, fostering collegiality, reducing complaints) and addresses LGBT business and trans staff-members' needs. We suggest that if employers adopt policy makers' positive workplace policies aiming to increase inclusivity, they may be able to realize positive organizational outcomes in their firms.
Keywords: K31; J11; D03; H11; H5; I18; J15; I31; 330; self-esteem; positive actions; workplace guide; gender identity